Subtle effects of acetone and amitraz on sucrose sensitivity and recall in honey bees - Ethan W. Huang; Susan E. Fahrbach (Scientific Reports)
Abstract Amitraz is a formamidine acaricide applied to hives to manage Varroa destructor, an ectoparasite of honey bees. As a high affinity octopaminergic agonist it is potentially neuroactive. Previous studies have described various effects or no effects of exposure to amitraz on honey bee sucrose sensitivity, learning, and memory but have not factored in age at exposure as a variable. This study conducted gustatory response assays, learning trials, and memory recall trials to examine the effects of amitraz on honey bee behavior. Topical application of acetone, the solvent vehicle, decreased sucrose sensitivity in newly emerged and foraging age honey bees; addition of amitraz to the acetone restored sucrose sensitivity to levels shown by untreated controls. Amitraz produced subtle effects on learning and memory in intermediate age and foraging age bees, whereas acetone treatment alone hindered performance. These results are consistent with prior demonstrations that stimulation of octopamine receptors increases sensitivity to sucrose but do not allow us to assess if amitraz facilitates olfactory learning. The effects of acetone were surprising, given its prior use as a neutral solvent in insect behavioral and toxicological studies. The results support use of alternative solvent vehicles in future studies.